(untitled) (UNED Research Journal, 2019)
Introduction: Mineralization is an essential process that improves the physical and chemical properties of soils through the recovery of biological activity and soil fertility, obtaining mainly mineral nitrogen used by plants. Objective: To determine the nitrogen contribution of green bean stubble (Phaseolus vulgaris) in an Andisol soil in San Ramón, Alajuela, Costa Rica. Methods: We did a chemical analysis (pH, acidity, Ca, Mg, K, P, Cu, Fe, Zn, Mn) on the soil before and after the experiment; and measured mineralization of the stubble incorporated in field plots after 10, 20 and 30 days Results: The highest nitrogen contribution was at 30 days with 3,4% of the nitrogen contained in the stubbles, i.e. 79% of the total nitrogen. Conclusions: microbial activity, decomposition, nitrogen availability and use of carbon are best after 30 days.